Prevalence of Cardiovascular Risk Factors in Elderly Population in Amirshahr (2007) - Seyed Reza Hosseini; Ali Zabihi; Ali Bijani (University of Social Welfare & Rehabilitation Sciences, 2009)
Objectives: This study has been carried out to assess the prevalenceof cardiovascular risk factors in the elderly people in Amirshahr city. Methods & Materials: In this descriptive cross- sectional study, 1019 people over 60 years old in Amirshahr city were assessed. Amirshahr has 2000 elder people over 60 (53.5% male and 46.5% female) .Data were collected using standard questionnaire included questions about demographic characteristics and risk factors of CVD. Questionnaires were filled in by trained questionerers during the interviews with elderly people or with informed person. Results: In this study, 604(59.3%) were male and 415(40.7%) female. Mean age of the elderly population was 70±7 years old (range 60-97 year). Most of them (55%) were in the age group (65-74). The prevalence of cardiovascular risk factors were overweight andobesity (44.1%), hypertension (HTN) (23.9%), Diabetes Mellitus (DM) (23.5%), and smoking (18%). Frequency of HTN (P=0.07), DM and obesity (P=0.000) in female population were more than male and smoking (P=0.000) in male population was more than female population. Of total subjects, 71.1% had 2 or 3 cardiovascular risk factors contemporaneous. Twenty five percent of geriatric population don’t have any insurance. Conclusion: With respect to findings of this study and high prevalence of cardiovascular risk factors, screening programs and preventive measures are necessary in elderly population.